2015
DOI: 10.4049/jimmunol.1500861
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF and GM-CSF in Neutropenia

Abstract: Granulocyte Colony Stimulating Factor (G-CSF) and Granulocyte/Macrophage Colony Stimulating Factor (GM-CSF) are used widely to promote the production of granulocytes or antigen presenting cells (APC). The Food and Drug Administration approved G-CSF (filgrastim) for the treatment of congenital and acquired neutropenias and for mobilization of peripheral hematopoietic progenitor cells for stem cell transplantation. A polyethylene glycol modified (PEGylated) form of G-CSF is approved for the treatment of neutrope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
226
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(242 citation statements)
references
References 118 publications
8
226
3
5
Order By: Relevance
“…Numerous studies have shown that GM-CSF or G-CSF plays the central role in the regulation of cisplatin-induced granulocytopenia [11,12]. Mobilization of granulocytes and their progenitors from bone marrow to the blood stream is induced by GM-CSF or G-CSF [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that GM-CSF or G-CSF plays the central role in the regulation of cisplatin-induced granulocytopenia [11,12]. Mobilization of granulocytes and their progenitors from bone marrow to the blood stream is induced by GM-CSF or G-CSF [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…G(M)-CSF signals through their each specific dimeric receptors to activate intracellular Janus kinase (JAK)/signal transducer and activator of transcription (STAT)/extracellular signal-regulated kinase (ERK) and phosphatidylinositol 3-kinase signaling. 2 For many functions, G-CSF and GM-CSF can crosscover. For some functions, they cannot.…”
Section: Introductionmentioning
confidence: 99%
“…Both G-CSF and GM-CSF are glycoproteins secreted from activated immune and endothelial cells sharing high sequence homology, both acting to promote the production, mobilization, and differentiation of hematopoietic stem cells. Both are used in recombinant form for the treatment of neutropenia and for mobilization of hematopoietic stem cells to the peripheral blood in transplantation [8]. CNS protective and recovery-promoting modulatory effects described for G-CSF on neurogenesis, angiogenesis, and immune activity in animal models of stroke, Alzheimer disease, and traumatic brain injury [9,10] have prompted its experimental use among stroke patients, with a lack of clear beneficial results to date [11].…”
Section: Discussionmentioning
confidence: 99%